DIGITAL TRANSFORMATION FOR SUSTAINABILITY BUSINESS ANALYSIS WITH GLOBAL REPORTING INDEX (GRI) STANDARD (CASE STUDY AT PT DATASCRIP) - Danang Kurniawarman (Universitas Islam Lamongan, 2024)
PT Datascrip, a trading company, realizes the importance of maintaining its business sustainability and decided to undergo digital transformation as an effort to strengthen its business performance in terms of sustainability since 2018. In its digital transformation, PT Datascrip made some changes in its business processes in order to support efficiency and business competitiveness. With digital transformation, PT Datascrip can optimize its business processes by using environmentally friendly technologies, such as the use of digital technologies to reduce paper consumption. PT Datascrip also adopts a data-driven approach to support sustainable decision-making, such as the use of data to identify risks and opportunities in environmental and social aspects. In this context, the integration of GRI Standards becomes important in reporting the company's sustainability performance transparently and accurately. By using GRI Standards, PT Datascrip can strengthen the credibility of the company's sustainability report and increase transparency in reporting sustainability performance. The transformation measurement can prove that digital transformation and the integration of ESG principles by using GRI Standards as a reference can strengthen its business performance in terms of sustainability. Through this approach, PT Datascrip can improve efficiency, improve the quality of sustainability reports, and create long-term value for all stakeholders of the company.